2016
DOI: 10.1186/s12944-016-0353-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selective LDL apheresis on serum chemerin levels in patients with hypercholesterolemia

Abstract: BackgroundSelective low-density lipoprotein (LDL) apheresis is commonly used to treat patients with familial hypercholesterolemia (FH). Chemerin is an adipokine with putative roles in the regulation of lipid metabolism.MethodsIn our pilot study, we measured serum chemerin levels by enzyme-linked immunosorbent assay in six severe heterozygous FH patients before and after their first LDL apheresis treatments using the technique of direct adsorption of lipoproteins (DALI).ResultsThe first treatment sessions decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…This suggests that chemerin is involved in the HDL maturing process [ 123 , 124 ]. LDL apheresis lowered circulating chemerin, implying that chemerin is bound, at least partly, to lipoproteins [ 125 ]. Future studies should investigate this possibility.…”
Section: Potential Role Of Chemerin In Metabolic and Cardiovascular D...mentioning
confidence: 99%
“…This suggests that chemerin is involved in the HDL maturing process [ 123 , 124 ]. LDL apheresis lowered circulating chemerin, implying that chemerin is bound, at least partly, to lipoproteins [ 125 ]. Future studies should investigate this possibility.…”
Section: Potential Role Of Chemerin In Metabolic and Cardiovascular D...mentioning
confidence: 99%
“…In addition to that, it reduces the level of lipoprotein (a) (Lp(a)) [ 23 ], known as an individual cardiovascular risk factor also in FH patients [ 24 , 25 ], as well as very low-density lipoprotein levels (VLDL), also containing ApoB, by 70% [ 26 ]. During apheresis, the level of protein-like components causing cardiovascular diseases is decreased in the serum; thus, the treatment has an evidently beneficial anti-atherosclerotic impact [ 27 ]. The serum levels of inflammatory cytokines and oxidative stress are reduced [ 28 ].…”
Section: Treatments Of Familial Hypercholesterolemiamentioning
confidence: 99%
“…Beyond its lipid lowering efficacy, LDL apheresis affects several pro‐ and anti‐inflammatory factors involved in the pathophysiology of human atherosclerosis including the complement cascade, the cytokine network and several other inflammatory mediators. Several studies demonstrated the benefits of LDL apheresis on these factors, most likely due to adsorption of the mediators to the columns . This could potentially confer additional benefits for these patients by decreasing the progression of arteriosclerosis, in addition to lowering their LDL cholesterol …”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated the benefits of LDL apheresis on these factors, most likely due to adsorption of the mediators to the columns. 5,6 This could potentially confer additional benefits for these patients by decreasing the progression of arteriosclerosis, in addition to lowering their LDL cholesterol. 7 Free radicals play an important role in the pathogenesis of atherosclerosis.…”
mentioning
confidence: 99%